2017
DOI: 10.1016/j.smallrumres.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin from slow-release implants did not influence the gene expression of the lipopolysaccharide receptor complex in the choroid plexus of seasonally anoestrous adult ewes subjected or not to a systemic inflammatory stimulus

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…It should be mentioned, that leptin had no effect on TLR4 , which is known as an LPS receptor [ 48 ]. However, TLR4 expression increased under LPS-challenge, what was in agreement with our previous studies [ 49 ]. This increase was stronger during SD than LD, which was discussed in our recent work [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It should be mentioned, that leptin had no effect on TLR4 , which is known as an LPS receptor [ 48 ]. However, TLR4 expression increased under LPS-challenge, what was in agreement with our previous studies [ 49 ]. This increase was stronger during SD than LD, which was discussed in our recent work [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Plasma cortisol and prolactin concentrations were determined according to the method previously described for cortisol [ 49 ] and prolactin [ 70 ]. The sensitivity of the assay for cortisol and prolactin was 0.95 and 2 ng/mL, and the intra- and inter-assay coefficients of variation were 10 and 12%, and 9 and 12%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, because melatonin significantly decreased cortisol plasma concentration in socially isolated ewes (Guesdon et al 2013) and corticosteroids (dexamethasone) pretreatment reduced the expression of AQP4 protein in the ovine cerebral cortex (Ron et al 2005), we considered also the potential effect of stress. The concentration of cortisol in blood plasma of sheep used in our experiment was measured and results were published by Kowalewska et al (2017). The similar low levels of cortisol demonstrated in blood plasma of control (10.8 ± 1.9 ng/ml) and melatoninimplanted (10.9 ± 1.2 ng/ml) ewes rather exclude the cortisol effect.…”
Section: Discussionsupporting
confidence: 54%
“…This complex transfers LPS to myeloid differentiation factor 2 (MD-2) and toll-like receptor-4 (TLR4), leading to LPS internalization and activation of NF-κB and the mitogen-activated protein kinase (MAPK) pathway [108,109]. Studies showed that systemic injection of LPS resulted in upregulation of TLR1, TLR3, TLR4, CD14, COX-2, IκBα in the CP cells which may lead to decreased expression of occludin [110][111][112][113][114][115][116]. In addition, there is evidence that activation of NF-κB upregulates matrix metalloproteinase-9 (MMP-9) production and induces claudin-5 degradation leading to alteration of the B-CSF barrier [117].…”
Section: Systemic Inflammationmentioning
confidence: 99%